2017
DOI: 10.17516/1997-1389-0026
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Toxicological Properties of P(3HB-co-4HB) Electrospun Membranes as an Experimental Wound Dressings

Abstract: Non-woven experimental samples of wound dressings, made from natural degradable polymers, were produced and investigated. High-porous membranes were obtained by electrostatic formation of solutions of copolymers of 3-hydroxybutyrate-co-4-hydroxybutyrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For effective regeneration of injured skin, novel material scaffolds are required to fulfil the antimicrobial potential, have no toxic effects, provide good mechanical support and sufficient elasticity to fit the wound shape. Shishatskaya et al [ 132 ] reported that P(3HB- co -4HB) intended for skin repair does not change the biological value of human blood cells. Also, P(3HB- co -4HB) has no toxic effect on the membrane and blood cells, therefore the development of P(3HB- co -4HB) scaffolds has the potential to meet the requirements for tissue regeneration and bioengineering.…”
Section: Biomedical Applications Of P(3hb -Co- mentioning
confidence: 99%
“…For effective regeneration of injured skin, novel material scaffolds are required to fulfil the antimicrobial potential, have no toxic effects, provide good mechanical support and sufficient elasticity to fit the wound shape. Shishatskaya et al [ 132 ] reported that P(3HB- co -4HB) intended for skin repair does not change the biological value of human blood cells. Also, P(3HB- co -4HB) has no toxic effect on the membrane and blood cells, therefore the development of P(3HB- co -4HB) scaffolds has the potential to meet the requirements for tissue regeneration and bioengineering.…”
Section: Biomedical Applications Of P(3hb -Co- mentioning
confidence: 99%